The Influence of Leadership Style and Career Development on Employee Competence Through Job Satisfaction as a Mediating Variable: JEL Classification: M12, M54, J24, J28, O15 - Jimmy Gunawan; Edy Hartono; Kartono Kartono (Journal La Bisecoman, 2025)
This research is motivated by the importance of human resources in achieving organizational effectiveness and competitive advantage. In the oil and gas industry, such as PT Pertamina EP Zona 4 Prabumulih, employee competency is a strategic factor in ensuring the company's operational success. However, complex organizational dynamics require an adaptive leadership style and a sustainable career development system to improve the quality of human resources. Based on this phenomenon, this study aims to analyze the influence of leadership style and career development on employee competency, as well as to examine the role of job satisfaction as a mediating variable at PT Pertamina EP Zona 4 Prabumulih. This study uses a quantitative approach. Data were collected by distributing questionnaires to PT Pertamina EP Zona 4 Prabumulih employees. Data analysis techniques were carried out using Partial Least Square – Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4.0 software. The results of the study indicate that (1) leadership style does not significantly influence employee competence, (2) career development does not significantly influence employee competence, (3) leadership style does not significantly influence job satisfaction, (4) career development does not significantly influence job satisfaction, and (5) job satisfaction does not mediate the influence of leadership style and career development on employee competence.